2015
DOI: 10.5604/15093492.1186813
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Hip Rotation Range-of-Motion Impairment and Low Back Pain. A Literature Review

Abstract: The precise assessment of hip rotation ROM, especially hip internal rotation ROM, must be included in the examination of patients with LBP symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 32 publications
0
31
0
1
Order By: Relevance
“…Given the recent evidence associating hip ROM deficits and athletic injuries, future research in warranted in this population. [13][14][15][50][51][52]20,21 Also, attempts to further classify the recreational WT participant according to the type of weight training and level of training may assist in providing a better understating of subgroups based on WT activities. This may provide insight into common mechanisms of injury related to specific weight training activities and help guide injury prevention strategies.…”
Section: Future Researchmentioning
confidence: 99%
“…Given the recent evidence associating hip ROM deficits and athletic injuries, future research in warranted in this population. [13][14][15][50][51][52]20,21 Also, attempts to further classify the recreational WT participant according to the type of weight training and level of training may assist in providing a better understating of subgroups based on WT activities. This may provide insight into common mechanisms of injury related to specific weight training activities and help guide injury prevention strategies.…”
Section: Future Researchmentioning
confidence: 99%
“…Direction of hip rotation, early lumbopelvic motion, and LBP have gender‐specific associations . In a study of gender differences, Gombatto et al compared LBP symptoms in 27 males and 19 females using three dimensional kinematic assessment of motion during hip external rotation.…”
Section: Secondary Subgroupmentioning
confidence: 99%
“…9,44-63 One hypothesis to explain this link between reduced hip range of motion and LBP is the reduced hip motion results in compensatory lumbar spine motion leading to the development of LBP. [51][52][53] A growing body of literature suggests a link between hip range of motion and LBP. Hip range of motion in subgroups of people with LBP have less: active internal rotation, 54,55 passive internal rotation, 51,56 lead leg active and passive internal rotation, 57-59 dominant leg active and passive internal rotation, 54 hip flexion, 60 passive hip extension, 61 and total hip rotation.…”
Section: Lbp Associated With Reduced Hip Range Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on hip internal rotation range of motion (Hip IR ROM) has shown that muscle strength asymmetry is associated with posture 7 ) . Therefore, the effect of exercise therapy on asymmetry of Hip IR ROM 8 ) should be considered when evaluating low back pain 9 ) . However, the effect of Hip IR ROM on other body functions remains unknown.…”
Section: Introductionmentioning
confidence: 99%